(untitled) (American Journal of Islam and Society, 2017)
Tristan James Mabry’s research investigates whether Muslim populations are exceptionally resistant to ethnonationalism, which he assumes to be more conducive to a liberal democratic form of government than any concept of community defined in terms of a shared religion. He concludes that Muslims are not immune to it, and that the determining factor in whether a Muslim community will organize itself according to ethnonationalism instead of Islamism – Mabry apparently considers these the only modes worth mentioning – is whether they develop a print culture in their local vernacular. Ultimately, the author concludes that nationalism founded upon ethnic solidarity is inherently superior to alternative sociopolitical models, and therefore advocates promoting local ethnonationalisms as a strategy to prevent Muslims from organizing themselves in terms of shared religious identity (p. 202) ...